1951
DOI: 10.1002/jlac.19515710203
|View full text |Cite
|
Sign up to set email alerts
|

Über den sterischen Verlauf von Dien‐Synthesen mit acyclischen Dienen. Das Verhalten von trans,trans‐, cis‐ und cis,trans‐4‐Phenyl‐butadien‐1‐carbonsäure‐methylester bei der Dien‐Synthese

Abstract: Das Verhalten von trans,trnns-, trnns,cis-und cis,lrc~ns-4-Phenyl-butadien-1-carbonsaure-methylester bei der Dien-Synthese' Voii h u r t Alder iind illariciiiiie Schunuichei~ Oberfiicht 1. Die ~terooisoinoren Ester und Jlelcinalure-anhgdrid.TI. Die stercoisomercn Ester und Fumarslure-ester (-chlorid). 111. Der trans, trms-lhtcr und hialeinslure-ester. LV. Ditr sterisdicn Umlagerungen cler Addukte.lh allgenieinen Gesicht.spunktc, von clcnen tlic vorliegcnde Untcrriuchung aiisgeht und die Zielr, die sie aiistreb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

1951
1951
1969
1969

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…A corollary of this rule is that cis 1-substituted butadienes should form adducts in which the diene substituent is trans to the dienophile substituent. This has been found to be the case in the adducts of maleic anhydride with m-l-ethyl-1,3-butadiene (7), cis,trans-1,4-dimethyl-1,3-butadiene (57), trans,cfs-4-methyl-lphenyl-1,3-butadiene (37), methyl trans,m-l-phenyll,3-butadiene-4-carboxylate (36), and neoalloocimene (13).…”
Section: Orientation In Addition To Acyclic Dienesmentioning
confidence: 85%
See 2 more Smart Citations
“…A corollary of this rule is that cis 1-substituted butadienes should form adducts in which the diene substituent is trans to the dienophile substituent. This has been found to be the case in the adducts of maleic anhydride with m-l-ethyl-1,3-butadiene (7), cis,trans-1,4-dimethyl-1,3-butadiene (57), trans,cfs-4-methyl-lphenyl-1,3-butadiene (37), methyl trans,m-l-phenyll,3-butadiene-4-carboxylate (36), and neoalloocimene (13).…”
Section: Orientation In Addition To Acyclic Dienesmentioning
confidence: 85%
“…Alder has reported that several cis 1-substituted dienes, on being heated to high temperatures with maleic anhydride, give adducts of the trans diene (35,36). Epimerization may also occur during workup of the products: the l-phenyl-l,3-butadiene-acrolein adduct isomerizes from cis to trans during purification with sodium bisulfite (54), and alkaline hydrolysis of the cis adduct of cyclopentadiene and dimethyl maleate gives the trans diacid (103).…”
Section: A Scope Of the Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…C'est la raison qui nous a pousses a synthetiser et etudier les acides J e t K qui sont encore inconnus dans la litterature (schema 1). Nous les avons obtenus par action des organometalliques sur les anhydrides phknyl-3 [7] et methyl-6 phknyl-3 phtaliques [8]. La structure de ces acides dtoniques a ete prouvee par cyclisation intramoleculaire en fluorhone correspondante (Sl, VII), reaction qui n'est possible que lorsque le carboxyle est en position 2.…”
Section: Ha Hbunclassified
“…L'analyse donne les resultats suivants : calcule pour C,,H,,O, C : 78,94% H : 5,26% trouve C : 78,7 Yo H : 5,4 Yo c) Acide benzuyl-3 tliph&yl carboxylique-2 (schema 1, I, R = a, R' = A)ti) On prepare le bromure de phenylemagnesium de la facon habituelle a partir de I 7 g, (0, I I mole) de bromobenzene et 2,6 g (0,ll atgr) de magnesium dans 100 ml d'ether sec. On ajoute alors ce reactif en agitant vigoureusement a une suspension de 22,4 g (0,l mole) d'anhydride phenyl-3 phtalique[7], finement broye, dans 100 ml de benzene sec. 11 se produit un echauffement tres net.…”
unclassified